Accountability of Public Servants under Dominant Political Settlements of China: Effects, Challenges, and Issues. Issue 3 (23rd February 2017) - Hu, Chunyan
ABSTRACT: Some scholars think that accountability is attainable only under the electoral political system. However, it is argued that China could achieve some weak accountability even without general election system. How could this be achieved in China? The paper attempts to analyze this question with the following steps: first, it describes the specific accountability system by categorizing different approaches based on four dimensions, then focuses on the impacts that these approaches would have, which are based on finance, fairness and efficiency. It is concluded that under a dominant political settlement, only weak accountability exists in China, not real or strong accountability.